Optimising whole body computed tomography doses for paediatric trauma patients: a Swiss retrospective analysis. (1st June 2022) - Simma, Leopold; Fornaro, Juergen; Stahr, Nikolai; Lehner, Markus; Roos, Justus E; Lima, Thiago Viana Miranda
Abstract: We aimed to evaluate the impact of a low-dose whole-body computed tomography (WBCT) protocol on radiation doses in paediatric major trauma patients. Retrospective cohort study of paediatric trauma patients (<16 years) at a national level 1 paediatric trauma centre (PTC) over a 6 year period prior and post introduction of a low-dose WBCT protocol (2014–2019). Demographic data, patient characteristics, CT device, and exposure information including scan range, dose-length product, and volume CT dose index were collected. Effective dose (ED) and exposure parameters were compared before and after protocol introduction. Forty-eight patients underwent WBCT during the study period. Prior to introduction of the low-dose protocol ( n = 18), the ED was 20.6 mSv (median 20.1 ± 5.3 mSv [range 12.5–30.7]). After introduction of the low-dose WBCT protocol ( n = 30), mean ED was 4.8 mSv (median 2.6 ± 5.0 [range: 0.8–19.1]). This resulted in a reduction of 77% in mean ED ( p value <0.001). Significant radiation dose reduction of 77% can be achieved with low-dose WBCT protocols in PTCs.